Bartleby and me : reflections of an old scrivener - Talese, Gay (Mariner Books, 2023)
American journalist Gay Talese chronicles his pioneering career, marked by a fascination with the world's hidden characters, followed by an all-new, in-depth study of Nicholas, a New York doctor who blew up his Manhattan brownstone rather than sell it to pay a court-ordered sum in a divorce settlement.